Investigating the effect of business intelligence competency dimensions on marketing performance considering the mediating role of customer relationship management - Hossein Norouzi; Mobina Rahmani Gohar; Hossein Imanipour (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: Considering the changes that have happened in recent years in the business process, attention to the category of business intelligence has become an important issue. Therefore, the present study examines the effect of the competence dimensions of business intelligence on marketing performance, considering the mediating role of customer relationship management in tourism businesses.Methodology: The current research is a descriptive survey regarding the applied purpose. The study's statistical population comprised experts and marketing managers of tourism companies in Tehran. In order to collect data, 300 questionnaires were distributed online and face-to-face using the non-probability sampling method, and 253 questionnaires were analyzed by removing distorted and indifferent questionnaires. The structural equation modeling method and SPSS 26 and Smart PLS 3 software were used for data analysis.Findings: The findings showed that the competency of business intelligence has a positive and significant effect on marketing performance, and customer relationship management plays a mediating role in this relationship. This shows that one of the ways to improve marketing performance and create a sustainable competitive advantage for managers is to use business intelligence.Originality/Value: In today's highly competitive world, the quality and timeliness of business information in organizations determine the difference between survival and bankruptcy. Also, the great importance of business intelligence and the critical role that this concept can have in improving the marketing performance of business organizations have been less discussed. Therefore, the results of the current research can improve tourism companies' marketing performance by applying business intelligence.